CRISPR Start-Loss: A Novel and Practical Alternative for Gene Silencing through Base-Editing-Induced Start Codon Mutations - Siyu Chen; Wanhua Xie; Zhiquan Liu; Huanhuan Shan; Mao Chen; Yuning Song; Hao Yu; Liangxue Lai; Zhanjun Li (Elsevier, 2020)
CRISPR-Cas9-mediated gene knockout and base-editing-associated induction of STOP codons (iSTOP) have been widely used to exterminate the function of a coding gene, while they have been reported to exhibit side effects. In this study, we propose a novel and practical alternative method referred to as CRISPR Start-Loss (CRISPR-SL), which eliminates gene expression by utilizing both adenine base editors (ABEs) and cytidine base editors (CBEs) to disrupt the initiation codon (ATG). CRISPR-SL has been verified to be a feasible strategy on the cellular and embryonic levels (mean editing efficiencies up to 30.67% and 73.50%, respectively) and in two rabbit models mimicking Otc deficiency (Otc gene) and long hair economic traits (Fgf5 gene).